Biocompatible SiO2 in the Fabrication of Stimuli-Responsive Hybrid Composites and Their Application Potential - Hasan Ahmad (Journal of Chemistry)
Organic/inorganic hybrid composite materials have been extensively studied as they combine the properties of inorganic material and organic polymer. Among the inorganic material biocompatible silica (SiO2) is an interesting candidate for application in biotechnology because such material is wide spread in nature as well as in medicine. During the last few decades, stimuli-responsive polymers are drawing much attention from the researchers for application versatility such as target-specific delivery of drug and corrosion inhibitors. Considering the biocompatibility and many such important properties as high cargo loading capacity, long blood circulation lifetime, enhanced permeability and retention, mechanical strength, and easy processability, combination of SiO2 particles with stimuli-responsive polymers is gaining attention over the last decade. This review article will report the progress made towards the development and application of stimuli-responsive hybrid composites based on SiO2.